Pengaruh Jerat Stagflasi Pada Capaian Laju Investasi di Provinsi Jawa Timur Periode 2019-2022 - Anggun Wida Prawira; Syamsul Arifin (Journal of Business and Economics Research (JBE), 2023)
This study aims to determine the effect of the threat of stagflation on investment realization in East Java Province in 2019-2022. The data studied is quarterly secondary data (time series) from the first quarter of 2019 to the fourth quarter of 2022 with a total sample of 16 quarters (for each variable), sourced from the Central Statistics Agency (BPS) and the Investment and One-Stop Services Office (DPMPTSP). Data analysis techniques used descriptive statistics, classical assumption tests, statistical tests and multiple linear regression analysis which were processed using SPSS version 25 software. The results of this study obtained the Stagflation Threat of GRDP Economic Growth with a Sig. 0.990 > 0.05 so it partially has a positive but not significant effect on investment realization. As a result of obstacles to economic performance such as the Covid-19 pandemic. The Threat of Stagflation Inflation obtained Sig. 0.013 <0.05, so partially has a positive and significant effect on investment realization. East Java was able to rise amid rising inflation. The Threat of Stagflation of Economic Growth (GRDP) and Inflation obtained a Sig value of 0.027 <0.05 so that they simultaneously have a positive and significant effect on investment realization.